Three-dimensional supramolecular phosphomolybdate architecture-derived Mo-based electrocatalytic system for overall water splitting. Issue 4 (13th February 2018) - Mei, Mingliang; Xu, Xinxin; Wang, Yun; Wang, Xinjiao; Huo, Yuqiu
Abstract : With phosphomolybdate supramolecular architecture-derivedMo 2 C@NC andMoO 2 @NC as cathode and anode, an efficient electrolyzer was constructed, which possessed excellent overall water splitting activity. Abstract : With hydrogen bond-directed three-dimensional phosphomolybdate-based supramolecular architecture as a precursor, a Mo2 C composite material (Mo 2 C@NC ) supported by nitrogen-doped carbon matrix was fabricated successfully through calcination. In this composite material, Mo2 C particles with size about 5 to 8 nm disperse evenly in the framework of nitrogen-doped mesoporous carbon matrix. In acid media, to achieve a current density of 10 mA cm −2, the overpotential required was 142 mV with a Tafel slope of 63 mV dec −1 . Under basic conditions, the overpotential reduced to as low as 56 mV with a Tafel slope of 59 mV dec −1 . To realize overall water splitting, MoO2 -based composite material (MoO 2 @NC ) with nitrogen-doped carbon as matrix was obtained using the same precursor asMo 2 C@NC .MoO 2 @NC exhibits excellent oxygen evolution reaction (OER) performance with an over potential of 302 mV. WithMo 2 C@NC as cathode andMoO 2 @NC as anode, an efficient electrolyzer was constructed, which required a cell voltage of 1.60 V to achieve a current of 10 mA cm −2 in 1.0 M KOH. Furthermore, besides overall water splitting, Mo 2 C@NC also shows striking catalytic removal property towards 4-nitrophenol and Rhodamine B.